(untitled) (MMIT Proceedings, 2024)
One of the important pedagogical technologies is the development of entrepreneurial games in order to increase students’ interest in science, to help them master it, to introduce the spirit of creativity into the educational process, and to introduce it into education. In this regard, the article briefly gave examples of these three methods, organized entrepreneurial games with students, and developed conclusions and proposals.